Green Synthesis of Carbon Dots from Grapefruit and Its Fluorescence Enhancement. (29th June 2020) - Huo, Xinzhu; He, Yuxuan; Ma, Shiqi; Jia, Yingying; Yu, Jiaming; Li, Yu; Cheng, Qian
Abstract : In this study, undoped carbon quantum dots (UCQDs, UCQDs-peel) and N-doped carbon dots (NCQDs) were prepared by a facile one-pot environmentally friendly hydrothermal method using grapefruit as carbon sources in the absence and presence of area, respectively. The structure, morphology, and fluorescence properties of three samples were characterized by Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), and photoluminescence (PL). It was found that three types of CQDs could emit blue fluorescence with different intensities when irradiated with ultraviolet light. Compared to the luminescence properties of UCQDs, NCQDs, and UCQDs-peel, it can be seen that the fluorescence intensity of NCQDs was strongest due to the presence of NH and C-N bonds.